A Global Strategy to Manage the Long-Term Risks of COVID-19 - Agarwal, Ruchir (IMF Working Papers; Working Paper, 2022)
The pandemic is not over, and the health and economic losses continue to grow. It is now evident that COVID-19 will be with us for the long term, and there are very different scenarios for how it could evolve, from a mild endemic scenario to a dangerous variant scenario. This realization calls for a new strategy that manages both the uncertainty and the long-term risks of COVID-19. There are four key policy implications of such as strategy. First, we need to achieve equitable access beyond vaccines to encompass a comprehensive toolkit. Second, we must monitor the evolving virus and dynamically upgrade the toolkit. Third, we must transition from the acute response to a sustainable strategy toward COVID-19, balanced and integrated with other health and social priorities. Fourth, we need a unified risk-mitigation approach to future infectious disease threats beyond COVID-19. Infectious diseases with pandemic potential are a threat to global economic and health security. The international community should recognize that its pandemic financing addresses a systemic risk to the global economy, not just the development need of a particular country. Accordingly, it should allocate additional funding to fight pandemics and strengthen health systems both domestically and overseas. This will require about USD 15 billion in grants this year and USD 10 billion annually after that.